2021
DOI: 10.33785/ijds.2021.v74i01.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of FMD vaccination stress on milk production in crossbred dairy cattle of Kerala

Abstract: Foot and mouth disease (FMD) is a contagious viral disease affecting cloven-footed animals which is endemic in India. The primary disease control strategy in India is mass vaccination using oil adjuvant killed FMD vaccine containing O, A and Asia 1 serotypes. Variations in milk yield following vaccination with oil adjuvant killed FMD vaccine was studied in 80 crossbred cattle, maintained at Livestock Research Station, Thiruvazhamkunnu for eight days. The study was conducted in August 2019. Rectal temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…The overall milk yield of the herd recovered to pre-vaccination levels by the sixth day following vaccination, with the greatest losses occurring on the rst day after vaccination, with a mean of 0.58 ± 09 kg. Over the time period, an average cumulative output loss of 1.93 kg per animal was determined (Pramod et al, 2021). Various authors reported a decrease in milk yield after vaccination, which corroborated our study.…”
Section: Discussionsupporting
confidence: 90%
“…The overall milk yield of the herd recovered to pre-vaccination levels by the sixth day following vaccination, with the greatest losses occurring on the rst day after vaccination, with a mean of 0.58 ± 09 kg. Over the time period, an average cumulative output loss of 1.93 kg per animal was determined (Pramod et al, 2021). Various authors reported a decrease in milk yield after vaccination, which corroborated our study.…”
Section: Discussionsupporting
confidence: 90%